التباطؤات الزمنية في ايرادات الصادرات النفطية واثرها في نمو الناتج المحلي الاجمالي في العراق للمدة ( 1970-2005) * - دراسة اقتصادية قياسية – (المجلة العراقية للعلوم الاقتصادية, 2018)
Exports play an important role in economic growth . It regards as engine of growth leading sector .In addition the study concentrates on different time lags in estimating the impacts of oil exports revenue on the growth of GDP in aggregate and sectorial levels. The aim of this study is to measure the impact of the time lags in response the growth of GDP in sectorial Level to the change in oil exports revenue. The hypothesis adopted in this Study states that: The growth of GDP in sectorial Levels do not responsiveness to the injections come from oil exports revenne.The main finding of this study is that the oil sector,which regards as a development pole,does not cause the spill-over effects because it does not reach to the development momentum stage.The study divided into three sections .The first sectionshed light on the reality of oil sector in Iraq. The second section deals with the theoretical framework. The third section discusses the results. Finally, the study ends with some conclusionsand suggestions .Key words : export , spill-over effects , revenue .